Respuesta :
Answer:
2k⋅(3k−7)⋅(k+4)
Step-by-step explanation:
STEP
1
:
Equation at the end of step 1
((6 • (k3)) + (2•5k2)) - 56k
STEP
2
:
Equation at the end of step
2
:
((2•3k3) + (2•5k2)) - 56k
STEP
3
:
STEP
4
:
Pulling out like terms
4.1 Pull out like factors :
6k3 + 10k2 - 56k = 2k • (3k2 + 5k - 28)
Trying to factor by splitting the middle term
4.2 Factoring 3k2 + 5k - 28
The first term is, 3k2 its coefficient is 3 .
The middle term is, +5k its coefficient is 5 .
The last term, "the constant", is -28
Step-1 : Multiply the coefficient of the first term by the constant 3 • -28 = -84
Step-2 : Find two factors of -84 whose sum equals the coefficient of the middle term, which is 5 .
-84 + 1 = -83
-42 + 2 = -40
-28 + 3 = -25
-21 + 4 = -17
-14 + 6 = -8
-12 + 7 = -5
-7 + 12 = 5 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -7 and 12
3k2 - 7k + 12k - 28
Step-4 : Add up the first 2 terms, pulling out like factors :
k • (3k-7)
Add up the last 2 terms, pulling out common factors :
4 • (3k-7)
Step-5 : Add up the four terms of step 4 :
(k+4) • (3k-7)
Which is the desired factorization
Final result :
2k • (3k - 7) • (k + 4)